Komunikasi Program Elektronik Siap Nikah dan Hamil (Elsimil) untuk Pencegahan Stunting di Kecamatan Ungaran Barat Kabupaten Semarang - Latifazzahra, Aisya; Hanani, Retna (Journal of Public Policy and Management Review, 2025)
The Government of the Republic of Indonesia has established Presidential Regulation Number 72 of 2021 concerning the Acceleration of Stunting Reduction. This regulation serves as a guideline for implementing interventions aimed at accelerating stunting reduction, with a target prevalence of 14% by 2024. In executing this intervention, the National Population and Family Planning Board (BKKBN) has developed the Elsimil program for prospective brides and grooms, which is also implemented in Ungaran Barat District. However, communication regarding this program has not been optimal. This research aims to analyze the communication of the Electronic Program for Ready to Marry and Pregnant (Elsimil) in Ungaran Barat District and to examine the supporting and inhibiting factors. The method used in this study is descriptive qualitative, with data collection conducted through interviews and documentation. The results indicate that communication regarding the Elsimil program in Ungaran Barat District has not yet reached its full potential. Aspects of communication clarity and consistency are lacking due to limited face-to-face interactions, and there are still prospective brides and grooms who do not adhere to online guidance properly.This study recommends that family assistance teams implement more flexible scheduling for support sessions, improve technology with more stable internet connections, and enhance collaboration with religious affairs offices (KUA) to make Elsimil certificates a mandatory document in the marriage registration process.